2013
DOI: 10.4103/0976-9668.107291
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-cyclodextrin complexation on solubility and enzymatic hydrolysis rate of icariin

Abstract: Objective:The aim of this work was to investigate the effect of β-cyclodextrin complexation on the solubility and hydrolysis rate of icariin.Material and Methods:The inclusion complex of icariin at the molar ratio of 1:1 was obtained by the dropping method and was characterized by differential scanning calorimetry. The solubility of icariin complex in water at 37°C was 36 times greater than that of free icariin. Enzymatic hydrolysis conditions were tested for the bioconversion of icariin by mono-factor experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…To the best of our knowledge, this ICA-PG exhibits a stronger solubilizing power to ICA than any other in the current report. For example, the solubility of ICA in the β-cyclodextrin inclusion complex is only 525.6 μg ml −1 , while that of the bare ICA is 14.6 μg ml −1 , 33 which is only about 0.61% of the values recorded in our study. It is widely accepted that solubility is one of the important parameters for achieving the desired (anticipated) pharmacological response.…”
Section: Discussioncontrasting
confidence: 72%
“…To the best of our knowledge, this ICA-PG exhibits a stronger solubilizing power to ICA than any other in the current report. For example, the solubility of ICA in the β-cyclodextrin inclusion complex is only 525.6 μg ml −1 , while that of the bare ICA is 14.6 μg ml −1 , 33 which is only about 0.61% of the values recorded in our study. It is widely accepted that solubility is one of the important parameters for achieving the desired (anticipated) pharmacological response.…”
Section: Discussioncontrasting
confidence: 72%
“…We must realize that the oral bioavailability rate is only 12.02% for 1 . Studies have shown the addition of cyclodextrins (CDs) to ICA can result in a vast increase in its water solubility, consequently achieving considerably better bioavailability ( Cui et al, 2013 ; Jin et al, 2013 ). The degradation of ICA into ICS in vivo promotes ICA absorption ( Cheng et al, 2015 ).…”
Section: Pharmacological Inhibition Of Ferroptosis For Treating Cardi...mentioning
confidence: 99%
“…Its intestinal absorption mechanism in rats was studied ( Zhang et al, 2012 ), when the complex was loaded into poly L-lactic acid scaffolds, the accumulated release percentage in vitro reached approximately 80% in 5 days ( Zhang et al, 2009b ). By using the dropping method, the inclusion complex of icariin with β -cyclodextrin was prepared, and the water solubility of icariin was increased only from 17 to 36 times though complexation ( Jin et al, 2012 ; Cui et al, 2013 ). Complexation of HP- β -cyclodextrin with icariin by stirring can only increase icariin’s water solubility about 4.3 times ( Wang et al, 2013b ).…”
Section: Introductionmentioning
confidence: 99%